2005
DOI: 10.1007/bf02430405
|View full text |Cite
|
Sign up to set email alerts
|

Study on structural, thermal, sintering and conductivity of Cu-Co doubly substituted Bi4V2O11

Abstract: Doubly substitution of vanadium by Cu and Co in the limit of 10% in Bi4V2O11, has led to the formation of the Bi4V1.8Cu0.2−xCoxO10.7 solid solution. X-ray diffraction shows that all the compositions present a tetragonal symmetry. The thermal analysis has revealed that the polymorph γ' phase, which is formed by a partial ordering of oxygen ions in the γ high temperature form, is stabilized at room temperature. The influence of sintering temperature on the microstructure of the samples was investigated by the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This may be related to changes in local symmetry as claimed from both XRD results that indicate a decrease in cell volume and the activity changes in the FT-IR spectrum after substitution. At high temperature, samples with x ≤ 0.3 show activation energies in the range of 0.26-0.42 eV, as generally obtained for γ-type phases [3,[19][20][21][22]. However, the activation energy values obtained for x > 0.3 are unusually higher.…”
Section: Electrical Conductivitysupporting
confidence: 62%
See 1 more Smart Citation
“…This may be related to changes in local symmetry as claimed from both XRD results that indicate a decrease in cell volume and the activity changes in the FT-IR spectrum after substitution. At high temperature, samples with x ≤ 0.3 show activation energies in the range of 0.26-0.42 eV, as generally obtained for γ-type phases [3,[19][20][21][22]. However, the activation energy values obtained for x > 0.3 are unusually higher.…”
Section: Electrical Conductivitysupporting
confidence: 62%
“…They were prepared in order to induce some additional disorder in the metal's site and then improve the conductivity. In a previous study, we have reported some data about double substitution of V 5+ by (Cu 2+ , Nb 5+ ) [20] and by (Cu 2+ , Co 2+ ) [21]. More recently, we have investigated the structural and ionic conductivity changes, when vanadium is doubly substituted by (Cu 2+ , Al 3+ ) in Bi4V1.8Cu0.2−yAlyO10.7+y/2 compounds [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the β-BINIVOX.10 sample shows a single endothermic peak at 396 • C assigned to the β → γ transition, while the occurrence of incommensurate → commensurate, γ → γ transition is detected in the compositional range 0.10 < x ≤ 0.20. It is interesting to note that the variation of transition temperature, T t , with Ni substitution shows a remarkable increase indicating an increased oxygen-vacancy ordering in the perovskite vanadate layers (18,19). This can also be correlated with the lattice expansion as Figure 3 shows UV-vis/DRS of the BINIVOX.x system for various compositions.…”
Section: Resultsmentioning
confidence: 88%
“…The two characteristic endothermic peaks clearly seen for the parent compound, Bi 4 V 2 O 11 (x=0) as well as the substituted photocatalyst with composition, x=0.05 are attributed to the consequent α→β and and β→γ transitions [23][24][25]. In addition, the heat flow per unit mass of the α→β transition is found to be nearly three orders of magnitude higher than that of the β→γ transition.…”
Section: Structural and Polymorphic Properties Of Photocatalystmentioning
confidence: 87%
“…In addition, the heat flow per unit mass of the α→β transition is found to be nearly three orders of magnitude higher than that of the β→γ transition. However, the β-BIMNVOX.10 photocatalyst shows a single endothermic peak 469 o C, assigned to the β→γ transition, while the occurrence of order → disorder, γ'→γ transition is observed for the γ'-BIMNVOX.13 phase [25,26]. UV-vis absorption spectra of BIMNVOX.x photocatalyst for various compositions are presented in Figure 5.…”
Section: Structural and Polymorphic Properties Of Photocatalystmentioning
confidence: 99%